Can't, Won't and What's the Point? A Theory of the UK Public's Muted Response to Austerity. Issue 2 (3rd April 2021) - Harrison, Kate
ABSTRACT: Since 2010 the UK government has undertaken extensive spending cuts which have manifested in significant reductions in welfare, local authority and justice system spending. The cuts have been linked with rising poverty, food bank use and serious health issues. Such extreme cuts are likely to affect how citizens view and interact with government. This paper argues that the theories of civic voluntarism, grievance and policy feedback in combination explain why austerity has provoked relatively little political participation in the UK.